Analysis of Online Urologist Ratings: Are Rating Differences Associated With Subspecialty?. (December 2020) - Zillioux, Jacqueline; Pike, C William; Sharma, Devang; Rapp, David E
Patients are increasingly using online rating websites to obtain information about physicians and to provide feedback. We performed an analysis of urologist online ratings, with specific focus on the relationship between overall rating and urologist subspecialty. We conducted an analysis of urologist ratings onHealthgrades.com . Ratings were sampled across 4 US geographical regions, with focus across 3 practice types (large and small private practice, academic) and 7 urologic subspecialties. Statistical analysis was performed to assess for differences among subgroup ratings. Data were analyzed for 954 urologists with a mean age of 53 (±10) years. The median overall urologist rating was 4.0 [3.4-4.7]. Providers in an academic practice type or robotics/oncology subspecialty had statistically significantly higher ratings when compared to other practice settings or subspecialties ( P < 0.001). All other comparisons between practice types, specialties, regions, and sexes failed to demonstrate statistically significant differences. In our study of online urologist ratings, robotics/oncology subspecialty and academic practice setting were associated with higher overall ratings. Further study is needed to assess reasons underlying this difference.